'A Different World' Individuals' experience of an integrated family intervention for psychosis and its contribution to recovery. (30th January 2012) - Allen, Jo; Burbach, Frank; Reibstein, Janet
<x xml:space="preserve">Abstract</x> Objectives. The aim of this study is to explore the meaning and significance of family interventions (FI) for the individual who experiences psychosis, and its significance for recovery. Design. A qualitative in‐depth interview design was used to explore individuals' experience of FI and its meaning to them. Methods. Seven individuals recovering from psychosis attending integrated FI sessions were interviewed using a semi‐structured interview schedule developed with service user input. Interviews were recorded, transcribed verbatim, and explored using Interpretative Phenomenological Analysis. Results. Three central themes highlighted the participants' experience: (1) They welcomed the shared experience with their families and felt contained and valued by the therapists; (2) They felt the sessions contributed to changed patterns of relating within the family and the creation of new meaning through the validation of multiple perspectives; and (3) They described how the family sessions supported a new positioning in the world, a sense of their own empowerment and personal responsibility, greater self‐acceptance, an increased ability to manage emotions, and hope for the future. Conclusions. Conditions in the family sessions provided an environment for changes in patterns of relating, personal meaning, and emotions to take place. Recovery, for these individuals, appeared to be about repositioning themselves in the world. The shared experience of sessions and the recognition of multiple perspectives within a containing environment may be related to recovery via the development of new perspectives and a more robust sense of self. This has clinical implications for the focus of FI sessions. Practitioner Points This study supports the use of various elements of integrated family interventions. Understanding service‐users' experience of family interventions and recovery processes can support the development of responsive clinicians and produce therapies that best support recovery processes.